Surface degradation of laminated metal 226Ra foils used in school sealed sources in the UK. (1st June 2022) - Whitcher, R; Page, R D; Cole, P R; Chappell, S; Hicks, J
Abstract: In the few years leading up to this research, CLEAPSS noticed a small but steadily increasing number of calls from UK schools regarding a red-brown discolouration on the surface of the foil of their radium source. There were no reports of this type of discolouration on foils of other radionuclides. CLEAPSS and the University of Liverpool collaborated to investigate the nature and cause of this discolouration and the likelihood that the foils were becoming unsafe. The evidence indicates that the discolouration is principally caused by some combination of silicon, sulfur and possibly lead from within the foil diffusing into the face layer. There is no indication currently that the face layers are fragmenting on these foils, but the longer-term integrity of the discoloured foils now becomes questionable. Given the age of the foils and the radiotoxicity of radium, the recommendation from this research is that discoloured foils should be taken out of service and disposed.